Staphylococcus aureus isolates from chronic osteomyelitis are characterized by high host cell invasion and intracellular adaptation, but still induce inflammation - Kalinka, Julia (2014)
Osteomyelitis is a severe inflammatory disease of the bone that is mainly caused by Staphylococcus aureus. Particularly, bone infections are difficult to treat and can develop into a chronic course with a high relapsing rate despite of antimicrobial treatments. The complex interaction of staphylococci with osseous tissue and the bacterial ability to invade host cells are thought to determine the severity of infection. Yet, defined bacterial virulence factors responsible for the pathogenesis of osteomyelitis have not been clearly identified. The aim of this study was to detect S. aureus virulence factors that are associated with osteomyelitis and contribute to a chronic course of infection. To this purpose, we collected 41 S. aureus isolates, each 11 from acute osteomyelitis (infection period less than 2 months), 10 from chronic osteomyelitis (infection period more than 12 months), 10 from sepsis and 10 from nasal colonization. All isolates were analyzed for gene expression and in functional in-vitro systems. Adhesion assays to bone matrix revealed that all isolates equally bound to matrix structures, but invasion assays in human osteoblasts showed a high invasive capacity of chronic osteomyelitis isolates. The high invasion rate could not be explained by defined adhesins, as all infecting strains expressed a multitude of adhesins that act together and determine the level of adhesion. Following host cell invasion isolates from chronic osteomyelitis induced less cytotoxicity than all other isolates and a higher percentage of Small-colony-variant (SCV)-formation, which represents an adaptation mechanism during long-term persistence. Isolates from acute and chronic osteomyelitis strongly produced biofilm and highly expressed agr and sarA that regulate secreted virulence factors and induced an inflammatory response in osteoblasts. In conclusion, chronic osteomyelitis isolates were characterized by a high host cell invasion rate, low cytotoxicity and the ability to persist and adapt within osteoblasts. Furthermore, isolates from both acute and chronic osteomyelitis strongly produced biofilm and induced high levels of host cell inflammation, which may explain tissue destruction and bone deformation observed as typical complications of long-lasting bone infections.